2018
DOI: 10.1016/j.jssr.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

More social studies?: Examining instructional policies of time and testing in elementary school

Abstract: Adding instructional time and holding teachers accountable for teaching social studies are touted as practical, logical steps toward reforming the age-old tradition of marginalization. This qualitative case study of an urban elementary school, examines how nine teachers and one administrator enacted district reforms that added 45 min to the instructional day and implemented a series of formative and summative assessments. Through classroom observations, interviews, time journals, and official school documents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 27 publications
(54 reference statements)
0
31
0
Order By: Relevance
“…While social studies instructional time declines, Schertz and McCormick (2013) found that "few classroom teachers are satisfied with social studies instruction at their institutions" (p. 85). Heafner (2018) noted that some teachers demonstrate ambition by seeking solutions to these challenges rather than succumbing to them. However, teacher motivation and determination must serve as driving forces for this ambitious resistance to restricting mandates (Barton and Levstik, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While social studies instructional time declines, Schertz and McCormick (2013) found that "few classroom teachers are satisfied with social studies instruction at their institutions" (p. 85). Heafner (2018) noted that some teachers demonstrate ambition by seeking solutions to these challenges rather than succumbing to them. However, teacher motivation and determination must serve as driving forces for this ambitious resistance to restricting mandates (Barton and Levstik, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past studies show the pressure on schools to perform well in the tested subjects of reading/language arts, mathematics, and science impacts both the schedule (i.e., time allocated to instruction) and the actual amount of time spent teaching social studies (Abrams et al, 2003;Bailey et al, 2006;Burroughs et al, 2005;Heafner, 2018;Hong & Hamot, 2020;Houser et al, 2017;Kavanagh & Fisher-Ari, 2018;Leming et al, 2006;Lintner, 2006;Pace, 2012;Pascopella, 2005;Pedulla et al, 2003;Segail, 2003;VanFossen, 2005;Vogler, 2003;Vogler & Virtue, 2007;vonZastrow & Janc, 2004;Zamosky, 2008). Lintner (2006) found in a study of Kindergarten through fifth-grade social studies in South Carolina that "with such a tremendous emphasis being placed on reading, writing, and math, social studies has to fight for instructional time" (p. 3).…”
Section: Impact Of Accountability Testing On Social Studiesmentioning
confidence: 99%
“…Past studies show the pressure on schools to perform well in the tested subjects of reading/language arts, mathematics, and science impacts both the schedule (i.e., time allocated to instruction) and the actual amount of time spent teaching social studies Bailey, Shaw, & Hollifield, 2006;Burroughs, Groce, & Webeck, 2005;Heafner, 2018;Houser, Krutka, Roberts, Pennington, & Coerver, 2017;Kavanagh & Fisher-ari, 2018;Leming, Ellington, & Schug, 2006;Lintner, 2006;Pace, 2012;Pascopella, 2005;Pedulla et al, 2003;Segail, 2003;VanFossen, 2005;Vogler, 2003;Vogler & Virtue, 2007;vonZastrow & Janc, 2004;Zamosky, 2008). Lintner (2006) found in a study of Kindergarten through fifth-grade social studies in South Carolina that "with such a tremendous emphasis being placed on reading, writing, and math, social studies has to fight for instructional time" (p.3).…”
Section: Impact Of Accountability Testing On Social Studiesmentioning
confidence: 99%
“…What is interesting is the lack of agreement that principals had regarding the perceived barriers affecting time allocated for social studies. Much has been made about the negative impact that federal and state-mandated testing has had on non-tested subjects such as social studies (Abrams et al, 2003;Bailey et al, 2006;Burroughs et al, 2005;Heafner, 2018;Houser et al, 2017;Kavanagh & Fisher-ari, 2018;Leming et al 2006;Lintner, 2006;Pace, 2012;Segail, 2003;VanFossen, 2005;Vogler, 2003;Vogler & Virtue, 2007;Zamosky, 2008); but for all that has been written about this unintended consequence of high-stakes testing (Au, 2009;Grant, 2006;Jones, Jones, & Hargrove, 2003;Madaus, 1988;McNeil, 2000;Popham, 2001;Smith, 1991), not even 40% of principals believed that this was an issue. As a matter of fact, the "no barriers" response was only 1.7% less than was the "testing mandates for content areas such as English and math" response and 1.7% greater than was the "non-inclusion of social studies in federal accountability mandates" response.…”
Section: Research Questionmentioning
confidence: 99%